Effect of acute hypobaric hypoxia on the endothelial glycocalyx and digital reactive hyperemia in humans - Johansson, Pär I.; Bergström, Anita; Aachmann-Andersen, Niels J.; Meyer, Martin A. S.; Ostrowski, Sisse R.; Nordsborg, Nikolai B.; Olsen, Niels V. (Frontiers in Physiology, 2014)
Introduction: Hypoxia is associated with increased capillary permeability. This study tested whether acute hypobaric hypoxia involves degradation of the endothelial glycocalyx. Methods: We exposed 12 subjects to acute hypobaric hypoxia (equivalent to 4,500 m for 2-4 hours) and measured venous blood concentrations of biomarkers reflecting endothelial and glycocalyx degradation (catecholamines, syndecan-1, soluble CD40 ligand, protein C, soluble thrombomodulin, tissue-type plasminogen activators, histone-complexed DNA fragments and nitrite/nitrate). Endothelial function was assessed by the hyperemic response to brachial artery occlusion by peripheral arterial tonometry. Results: Compared with normoxic baseline levels, hypoxia increased concentrations of syndecan-1 from 22 (95% confidence interval: 17-27) to 25 (19-30) ng/ml (p < 0.02) and protein C from 76 (70-83) % to 81 (74-88) % (p < 0.02). Nitrite/nitrate decreased from 23 (18-27) μM at baseline to 19 (14-24) μM and 18 (14-21) μM in hypoxia and recovery, respectively (p < 0.05). Other biomarkers remained unchanged. The post-occlusion/pre-occlusion ratio (reactive hyperemia index, RHI) decreased from 1.80 (1.52–2.07) in normoxia to 1.62 (1.28–1.96) after 2 to 4 hours of hypobaric hypoxia and thereafter increased to 2.43 (1.99-2.86) during normoxic recovery (p < 0.01). Conclusions: The increase in syndecan-1 and protein C suggests that acute hypobaric hypoxia produces minor degree of glycocalyx degradation and overall cellular damage. After hypoxia RHI rebounded to higher than baseline levels suggesting improved endothelial functionality.